Determination of acute sertraline intoxication by high-performance thin-layer chromatography - Turkmen, Zeynep; Arslan, Zeynep (JPC. Journal of planar chromatography, modern TLC, 2024)
Sertraline (SRT) is frequently used in the treatment of depression and other psychiatric disorders owing to its low side effects. However, many cases of SRT overdose and death have been reported, often accompanied by other drugs or alcohol. Suicide is the primary cause of death in most cases. Although SRT may have low potential for abuse, concerns have been raised recently about suicide as a potential side effect. Therefore, developing analytical techniques to detect and quantify SRT is important for forensic and clinical toxicology. This study aims to present a rapid and reliable high-performance thin-layer chromatography (HPTLC) method for the detection and quantification of SRT in urine samples. The developed method was validated according to Scientific Working Group for Forensic Toxicology guidelines. Linearity ranged between 2.5 and 125 ng/spot, mean recovery was 93.08%, and percent relative standard deviation (%RSD) values were less than 4. The validated method was applied successfully to the urine samples obtained from two authentic suicide cases involving SRT poisoning. SRT concentration was determined to be 205.3 ng/mL in case 1 and 722.7 ng/mL in case 2. The outcomes of this study may help determine SRT intoxication. In addition, we believe that the possible use of SRT should also be investigated in cases of attempted or completed suicide that are subject to forensic investigation. Even in such cases, the search for evidence of SRT in biological samples can help to clarify cases. The analytical method presented will also be useful for diagnosis in the emergency department and for psychiatric evaluation.